1994
DOI: 10.1002/ana.410360608
|View full text |Cite
|
Sign up to set email alerts
|

The role of calcium‐binding proteins in selective motoneuron vulnerability in amyotrophic lateral sclerosis

Abstract: The factors contributing to selective motoneuron loss in amyotrophic lateral sclerosis (ALS) remain undefined. To investigate whether calcium-binding proteins contribute to selective motoneuron vulnerability in ALS, we compared calbindin-D28K and parvalbumin immunoreactivity in motoneuron populations in human ALS, and in a ventral spinal cord hybrid cell line selectively vulnerable to the cytotoxic effects of ALS IgG. In human autopsy specimens, immunoreactive calbindin-D28k and parvalbumin were absent in moto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
213
1
7

Year Published

1996
1996
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 331 publications
(242 citation statements)
references
References 53 publications
11
213
1
7
Order By: Relevance
“…It has been extensively described that calcium dysregulation and excitotoxicity are 2 main pathogenic mechanisms of ALS pathology [45,46]. ALS-vulnerable spinal and brainstem MNs display low endogenous Ca 2+ buffering capacity, that is 5 to 6 times lower than that found in ALSresistant MNs (i.e., oculomotor MNs), making them more susceptible to excitotoxic insults [47]. NMDA receptor is considered to be 1 of the key elements in excitotoxiciy [46].…”
Section: Discussionmentioning
confidence: 99%
“…It has been extensively described that calcium dysregulation and excitotoxicity are 2 main pathogenic mechanisms of ALS pathology [45,46]. ALS-vulnerable spinal and brainstem MNs display low endogenous Ca 2+ buffering capacity, that is 5 to 6 times lower than that found in ALSresistant MNs (i.e., oculomotor MNs), making them more susceptible to excitotoxic insults [47]. NMDA receptor is considered to be 1 of the key elements in excitotoxiciy [46].…”
Section: Discussionmentioning
confidence: 99%
“…3,4,13 Motor cells are potentially highly vulnerable to changes in extracellular glutamate levels as they express a large number of calcium-permeable AMPA receptors 12,[31][32][33] and have limited capacity to buffer calcium. 34 Although astrocytes express functional glutamate receptors, they are normally more resistant to stimuli that are excitotoxic for neurons. However, in this study, we found that cultured astrocytes that express hSOD1 G93A or hSOD1 G85R become susceptible to concentrations of exogenous glutamate that are not detrimental for wild-type astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…All above commented data are consistent with the possibility that hippocampal neuronal death is mediated by TMTinduced intracellular Ca 2+ overload activating apoptotic pathways. The hypothesis that Ca 2+ -binding proteins such as CR which play a protective role against cell-deathinducing Ca 2+ overload has also been advanced in a series of neuropathological conditions including amyotrophic lateral sclerosis, ischaemia, AD and Parkinson's disease (Alexianu et al 1994;Mouatt-Prigent et al 1994;Yenari et al 2001;Attems et al 2008;Mattson 2007), and in experimental models of brain injury (Isaacs et al 1997;Dekkers et al 2004;Sasaki et al 2006), although this hypothesis has not been conclusively demonstrated. It is noteworthy in this respect that in the present experimental conditions CR-containing cells do not show signs of early commitment to death as indicated by experiments of doublelabelling for CR and annexin V.…”
Section: Discussionmentioning
confidence: 99%